1970
DOI: 10.1111/j.1432-1033.1970.tb01168.x
|View full text |Cite
|
Sign up to set email alerts
|

Messenger RNA in HeLa Cells:

Abstract: Messenger RNA (mRNA) and messenger like RNA (mlRNA) were investigated in the cytoplasm of HeLa cells while ribosomal RNA synthesis was arrested. Under these conditions, functional mRNA associated in polyribosomes and cytoplasmic free mlRNA are formed and can be labelled selectively to steady state.All cytoplasmic non-ribosomal RNA sedimenting a t more than 6-7 S exists in the form of ribonucleoprotein complexes which pre-exist in the cell, and are stable upon cell lysis, sedimentation and (after fixation) CsCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

1971
1971
1999
1999

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 172 publications
(66 citation statements)
references
References 44 publications
4
62
0
Order By: Relevance
“…The pellet containing mostly polyribosomes was suspended by gentle homogenisation in suspension buffer at a concentration of 10 A,,, units per ml. The upper third of the 40-min supernatant was recentrifuged in the Ti-60 rotor a t 60000rev./min for a further 140 min to remove ribosomal material and free messenger-like RNA * protein complexes [8] and served in the cell-free systems as the source of enzymes and tRNAs (180-min supernatant).…”
Section: Preparation Of Polyribosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pellet containing mostly polyribosomes was suspended by gentle homogenisation in suspension buffer at a concentration of 10 A,,, units per ml. The upper third of the 40-min supernatant was recentrifuged in the Ti-60 rotor a t 60000rev./min for a further 140 min to remove ribosomal material and free messenger-like RNA * protein complexes [8] and served in the cell-free systems as the source of enzymes and tRNAs (180-min supernatant).…”
Section: Preparation Of Polyribosomesmentioning
confidence: 99%
“…Aliquots were fixed with formaldehyde according to Spohr [8] and analyzed on glycerol gradients. The magnesium concentration of the remaining unfixed material was restored by overnight dialysis against suspension buffer containing 2 mM magnesium.…”
Section: Dissociation and Reassociation Of Po!yribosomesmentioning
confidence: 99%
“…Extensive investigations carried out in several laboratories over the last decades showed that mRNA exists in essentially two compartments of the cytoplasm; the translated mRNA in polyribosomes which is associated with a variety of translational-control factors forming an mRNP (m, messenger) upon dissociation of the ribosomes and the non-translated repressed mRNA associated with another set of protein and RNP factors, which keep it in a non-translatable status zn vitro and, most likely, in vivo (Spohr et al, 1970). The former mRNP includes ubiquitous factors common to all types of mRNA [cap-binding and poly(A)-binding proteins, initiation factors, etc.…”
mentioning
confidence: 99%
“…Duck erythroblasts and HeLa cells were labelled with 32P or 3H-uridine and RNA was extracted, purified and fractionated as previously described [3,13,191. Hybridization was carried out either in liquid phase and evaluated by the Sephadex technique [3] or on filters by the urea low-temperature technique [2] .…”
Section: Methodsmentioning
confidence: 99%